The Impact of the Waste Bank Program on Changes in Community Environmental Cleanliness Behavior - Syaiful Bachri; Rahmat Pannyiwi; Lorensius Lonik (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Environmental cleanliness is an important indicator of public health and quality of life. The problem of poorly managed waste is a major challenge in many urban areas, including Indonesia. One innovation to increase community participation in waste management is the waste bank program, a community-based waste collection, processing, and utilization system that provides economic incentives for residents. This study aims to determine the effect of the waste bank program on changes in environmental cleanliness behavior in three urban villages. The method used was a quantitative survey with a pretest-posttest design. The study sample consisted of 120 residents who actively participated in the waste bank program for at least 3 months. Data were collected through hygiene behavior questionnaires before and after participating in the program, as well as in-depth interviews with program managers to obtain supporting qualitative information. Data analysis was conducted using a paired t-test to determine significant differences in hygiene behavior before and after the program. The results showed a significant increase in all hygiene behavior indicators, including the habit of disposing of waste properly, sorting waste, and participation in environmental activities (p < 0.01). These findings demonstrate that the waste bank program is not only effective as a waste management tool but also plays a role in encouraging positive behavioral changes, increasing environmental awareness, and building a sustainable culture of community cleanliness. This research underscores the importance of program sustainability, community education, and local government support to ensure long-term impacts on environmental quality.